Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1055/s-0029-1241899
|View full text |Cite
|
Sign up to set email alerts
|

Wertigkeit der farbkodierten Duplexsonographie in Abhängigkeit der klinischen Vortest-Wahrscheinlichkeit bei Riesenzellarteriitis

Abstract: Taking into account pretest probability, an RCA can be accurately diagnosed or excluded by CDS in two thirds of patients without biopsy. When performed by an experienced investigator CDS is a basic part in the diagnosis of CDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Of a total of 16 primary studies that examined the diagnostic value of the halo sign demonstrated by temporal artery ultrasonograply versus the ACR 1990 criteria for the classification of vasculitis, used as a reference standard [3,5,6,16-28], only 9 studies met our inclusion/exclusion criteria [3,5,6,17-19,21,24,27]. To avoid duplicate reports on the same patients, one study [3] was excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of a total of 16 primary studies that examined the diagnostic value of the halo sign demonstrated by temporal artery ultrasonograply versus the ACR 1990 criteria for the classification of vasculitis, used as a reference standard [3,5,6,16-28], only 9 studies met our inclusion/exclusion criteria [3,5,6,17-19,21,24,27]. To avoid duplicate reports on the same patients, one study [3] was excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present meta-analysis further substantiate this algorithm. Moreover, in a recent study involving 182 patients from a single center, albeit not using the ACR criteria as the reference standard, it was found that GCA can be accurately diagnosed or excluded by ultrasonography, without biopsy, in two thirds of patients [28]. …”
Section: Discussionmentioning
confidence: 99%